Android-Based Musical Instrument Recognition Application For Vocational High School Level - Yusuf Kurnia; Toga Parlindungan Silaen (Komunitas Dosen Indonesia, 2021)
With the old way of learning and methods, Vocational High School students will be bored, especially in the field of Arts and Culture, which on average are considered difficult and not liked by most students. Therefore, it is necessary to make other learning media based on Android so that learning becomes more interesting and enjoyable. In addition, with this learning media, it is hoped that it can help children's creativity and thinking power, because it is equipped with several important components that can hone children's imaginative power such as pictures, videos in the material provided. Therefore, the authors design and create an application about interactive learning media that includes these components. This application will be aimed at the Vocational High School level with the title